Ambassador Animals Do Not Have a Clear Effect on Visitor Conservation Knowledge and Attitudes Toward Exotic Pets at a Zoo Exhibit - Kirsch, Daniel G.; MacPherson, Anna C.; Meyers, Caterina N.; Bowser, Sarah L.; Kross, Sara M. (Zoo biology, 2025)
ABSTRACT There is relatively little work examining visitor outcomes of ambassador animal programs, such as whether these programs are educationally effective or unintentionally promote exotic pet ownership. We designed a two‐way factorial experiment to test whether ambassador animals enhanced or detracted from the educational outcomes of a zoo exhibit. We surveyed 312 visitors at the Oakland Zoo at a static exhibit focused on the illegal wildlife trade. Participants were surveyed either before or after visiting the exhibit, with or without a trainer presenting either an ambassador ball python (Python regius) or yellow‐naped Amazon parrot (Amazona auropalliata). The survey assessed attitudes toward conservation, knowledge of conservation behavior, and the suitability of various species, including the ambassador species, as pets. We used an ANOVA to examine 299 complete surveys for differences between experimental groups' mean responses. There were no significant differences in conservation attitudes. Subjects demonstrated more knowledge of conservation behavior after leaving the exhibit, regardless of whether or not an animal was present. While the exhibit reduced favorable attitudes toward parrots as pets, ambassador animal presence neither positively nor negatively impacted on this effect. Participants who viewed a python were more likely to indicate that they viewed a python as a good pet. However, the sample expressed overall negative attitudes toward exotic pet ownership. This study suggests that ambassadors neither enhanced learning nor unintentionally promoted exotic pets. Further research is needed to understand the role of interpretive messaging when using ambassadors in an educational context. Overview of two‐way factorial experiment to evaluate how ambassador animals impact the educational outcomes of a zoo exhibit. Subjects were given a survey assessing attitudes toward exotic pets and knowledge of conservation before or after visiting the exhibit, with or without an animal present. Upon exiting the exhibit, subjects demonstrated higher conservation knowledge and less willingness to own exotic pets regardless of whether they experienced an ambassador demonstration: no impact of ambassador animals was detected.